Environmental Spatial Analysis of Water-Provisioning Ecosystem Carrying Capacity and Food-Crop Land Allocation in Dryland Agriculture In South Central Timor Regency, Indonesia - Robertho kadji; Ika Fitri Krisnasiwi; Bayu Mahendra (PT Keberlanjutan Strategis Indonesia, 2024)
Abstract:Water provisioning is a structural determinant of dryland-farming productivity in semi-arid Eastern Indonesia, yet the spatial coherence between water-provisioning ecosystem carrying capacity and the food-crop allocation prescribed by the regency Spatial Plan remains insufficiently quantified. This study evaluates the Water-Provisioning Ecosystem Service Index (IJL-PA) for South Central Timor (Timor Tengah Selatan, TTS) Regency under the three-proxy framework prescribed by Government Regulation No. 26 of 2025, focusing on the food-crop zone (P-1) overlaid on the dryland agriculture (PLK) land cover. The 393,233 ha regency was disaggregated through a GIS-based weighted overlay of landform (32 percent), natural vegetation (8 percent), and land cover (60 percent) layers, and subsequently intersected with the regency Spatial Plan and the PLK extent. The results indicate that 58.86 percent of TTS falls within the Low IJL-PA class and only 6.98 percent reaches the High or Very High class. Although the aggregate Water Carrying Capacity ratio (DDA) reaches 1.10, 20 of 32 sub-districts record a DDA below one, with Kokbaun reaching 0.13. Of the 41,315 ha food-crop allocation, 58.3 percent of the P-1 by PLK intersection (33,412 ha) is placed on Low to Very-Low IJL-PA, indicating a structural spatial mismatch that warrants explicit revision of the Spatial Plan and prioritization of soil-water conservation packages in the forthcoming Regional Environmental Protection and Management Plan.